Extending the two-stage information systems continuance model: incorporating UTAUT predictors and the role of context - Venkatesh, V.; Thong, J.; Chan, Frank; Hu, P.; Brown, S. (Blackwell Scientific Publications, 2011)
This study presents two extensions to the two-stage expectationconfirmationtheory of information systems (IS) continuance. First, we expand thebelief set from perceived usefulness in the original IS continuance model to includethree additional predictors identified in the unified theory of acceptance and use oftechnology, namely effort expectancy, social influence and facilitating conditions.Second, we ground the IS continuance model in the context of transactionalsystems that involve transmission of personal and sensitive information andinclude trust as a key contextual belief in the model. To test the expanded IScontinuance model, we conducted a longitudinal field study of 3159 Hong Kongcitizens across two electronic government (e-government) technologies thatenable citizens’ access to government services. In general, the results support theexpanded model that provides a rich understanding of the changes in the preusagebeliefs and attitudes through the emergent constructs of disconfirmationand satisfaction, ultimately influencing IS continuance intention. Finally, wediscuss the theoretical and practical implications of the expanded model.